Walking: towards a valuable academic life. Issue 2 (4th March 2022) - Manathunga, Catherine; Black, Alison L.; Davidow, Shelley
ABSTRACT: Frenetic digital timescapes reduce academic life to the endless achievement of metrics. These forces produce unsustainable work practices that disconnect us from ourselves, from ideas, from the natural world and from each other. While there is a substantial body of literature critiquing this, the use of arts-based inquiry into academic work is less common. In this article, we use slow 'thinking-in-movement' practices and arts-based methodologies to argue that beach walking enables us to resist the academic machine. We suggest that beaches act as liminal spaces where we may engage in post-feminist, new materialist c/a/r/tographies. Beach walking enables us to defamiliarize our bodies and interrupt the academic machine so that we might enact more embodied, contemplative ways of working. Written as a performative piece, this article intersperses citations of towards a valuable academic life. Come, join us as we walk …